Studi in silico tentang naringin sebagai reseptor anti-HER-2 dalam pengobatan kanker payudara - Abdurrahman, Abdurrahman; Rijal, Muh. Agus Syamsur; Yusuf, Helmy; Norhayati; Rizaldi, Gusti (Universitas Borneo Lestari, 2024)
Overexpression of Human Epidermal Receptor-2 (HER-2) is the cause of the development of breast cancer, so HER-2 can be a target for anticancer therapy. Trastuzumab is the drug of choice in inhibiting the HER-2 receptor and tyrosine kinase, but the weakness of this drug is that drug resistance can occur. Naringin has potential as a breast cancer therapy. The research aims to determine the inhibiting overexpression of the HER-2 receptor by naringin using in silico method. Molecular docking has been carried out by optimizing naringin and trastuzumab, preparing the HER-2 protein target (PDB ID 3PP0), validating the molecular docking protocol, and docking naringin and trastuzumab on HER-2. The research produced a binding energy of -8,66 kcal/mol, while the binding energies of the original ligand and trastuzumab to HER-2 were -9,94 kcal/mol and -5,87 kcal/mol, respectively. The binding energy shows that naringin has potential as an anti-breast cancer agent as indicated by its stronger affinity for HER2.